Decoupled Solar Energy Storage and Dark Photocatalysis in a 3D Metal–Organic Framework (Adv. Mater. 1/2023). Issue 1 (5th January 2023) - Stanley, Philip M.; Sixt, Florian; Warnan, Julien
Abstract : Charge Storage Long live the electron! Solar‐energy conversion and long‐term storage for on‐demand electrical and chemical energy are crucial toward decentralized energy distribution. In article number 2207280, Julien Warnan and co‐workers show how a hybrid material from a metal–organic framework and molecular rhenium complex enables light‐driven accumulation of long‐lived electrons. Full charge storage over several weeks is achieved as well as on‐demand "dark photocatalysis" for decoupled hydrogen evolution.